PELATIHAN MEMBACA AL-QURAN MELALUI METODE TILAWATI BAGI SISWA SMAN 2 PALANGKA RAYA - Wahyudi Wahyudi; Noorazmah Hidayati; Muhammad Fahrianor (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The main focus of this service is training in reading the Al-Quran using the Tilawati method for SMA Negeri 2 Palangka Raya, as the aim of this service is to arouse and increase students' interest and motivation in reading the Al-Quran, providing skills and understanding. in correct and appropriate reading makhorijul letters, in improving students' ability and skills in reading the Al-Quran using the Tilawati method. This service method uses the Service Learning (SL) method. Service learning is a form of learning process strategy that integrates the benefits of community service through appropriate learning and reflection, provides rich learning experiences, builds a sense of responsibility, and strengthens the community. As for the results of the implementation of this training activity, students with the recitation method saw their understanding improve much more and significantly after being given an explanation of how to read the Al-Quran very well and correctly so that it was in accordance with the makhorijul letters and tajwid. This was indicated by the few mistakes they read after given training using the recitation method.